MANAJEMEN LAYANAN KHUSUS PENDIDIKAN ASRAMA DI MADRASAH ALIYAH NEGERI INSAN CENDIKIA JAMBI - Marsadinda, Fadhilah; Fadlilah; Fransisko Chaniago (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of special dormitory education services at MAN Insan Cendikia Jambi, focusing on planning, implementation, and evaluation. The study employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation involving the principal, dormitory head, dormitory supervisors, and students. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the planning of dormitory education services is conducted systematically through coordination among the principal, dormitory head, and dormitory management based on the dormitory's vision, mission, and students' needs. The programs include daily, weekly, monthly, and annual activities, with the Gentala Arasy program serving as the flagship character development initiative. The implementation of services covers character and discipline development, academic support, health services, religious activities, life skills development, and the enhancement of Arabic and English language proficiency. However, several disciplinary violations by students were still identified. Evaluation is conducted periodically through supervision, monitoring, coaching, and evaluation meetings to assess program effectiveness and address implementation challenges. Overall, the management of special dormitory education services has been implemented effectively, although strengthening supervision and student guidance remains necessary to optimize the development of character, discipline, and independence.